Plate Heat Exchangers for Condensation Processes: Recent Developments and Future Perspectives - Arsenyeva, Olga; Kapustenko, Petro; Tovazhnyanskyy, Leonid (Book of abstracts of The 7th Sustainable Process Integration Laboratory (SPIL) Scientific Conference in Conjunction with Renewable Energy System for Residential Building Heating and Electricity Production (RESHeat) Workshop)

Mathematical Model of Energy Efficiency for the Intelligent Residential Heating Systems - Polyvianchuk, Andrii; Semenenko, Roman; Tur, Oleg; Arsenyeva, Olga (Abstracts of the 7th Sustainable Process Integration Laboratory (SPIL) Scientific Conference in Conjunction with Renewable Energy)

Grammatik in deutschen und niederländischen DaF-Lehrbüchern: Synergien für den Deutschunterricht - Blachut, Alisa; Topalović, Elvira; Uhrig, Sissy (Der Deutschunterricht)

Tethering chiral Rh diene complexes inside mesoporous solids: experimental and theoretical study of substituent, pore and linker effects on asymmetric catalysis - Kirchhof, Manuel; Gugeler, Katrin; Beurer, Ann-Katrin; Fischer, Felix Richard; Batman, Derman; Bauch, Soeren M.; Kolin, Sofia; Nicholas, Elliot; Schoch, Roland; Vogler, Charlotte; Kousik, Shravan R.; Zens, Anna; et al. (Catalysis Science Technology)
Improved enantioselectivity in the 1,2-addition was observed for chiral Rh norbornadiene catalysts immobilized on ordered mesoporous silica with small pores. Confinement effects were rationalized by experimental and computational studies.
Keywords: Catalysis

Evaluating the role of word-related parameters in the discriminative power of a novel nonword repetition task for bilingual children - Bloder, Theresa; Eikerling, Maren; Lorusso, Maria Luisa (Clinical Linguistics & Phonetics)

Methodical approach for the design and dimensioning of mechanical clinched assemblies - Zirngibl, Christoph; Martin, Sven; Steinfelder, Christian; Schleich, Benjamin; Tröster, Thomas; Brosius, Alexander; Wartzack, Sandro (Materials Research Proceedings)
The focus towards multi-material and lightweight assemblies, driven by legal requirements on reducing emissions and energy consumptions, reveals important drawbacks and disadvantages of established joining processes, such as welding. In this context, mechanical joining technologies, such as clinching, are becoming more and more relevant especially in the automotive industry. However, the availability of only few standards and almost none systematic design methods causes a still very time- and cost-intensive assembly development process considering mainly expert knowledge and a considerable amount of experimental studies. Motivated by this, the presented work introduces a novel approach for the methodical design and dimensioning of mechanically clinched assemblies. Therefore, the utilization of regression models, such as machine learning algorithms, combined with manufacturing knowledge ensures a reliable estimation of individual clinched joint characteristics. In addition, the implementation of an engineering workbench enables the following data-driven and knowledge-based generation of high-quality initial assembly designs already in early product development phases. In a subsequent analysis and adjustment, these designs are being improved while guaranteeing joining safety and loading conformity. The presented results indicate that the methodological approach can pave the way to a more systematic design process of mechanical joining assemblies, which can significantly shorten the required number of iteration loops and therefore the product development time.
Keywords: Joining; Structural Analysis; Machine Learning

Experimental investigation of the cause and effect relationships between the joint and the component during clinching - Steinfelder, Christian; Brosius, Alexander (Materials Research Proceedings)
The combination of the mechanical properties of a clinched joint and of the material surrounding the joint determine the resulting properties of the component and joint. The cause and effect relationships between the joint and the joint environment offers the possibility of a specific modification through an adaptation in the design process. In order to identify these cause and effect relationships and resulting interactions experimentally, numerous of experiments are required. In this publication, a concept for the automated manufacturing of head tensile test and shear tensile test specimens – from cutting to clinching – by using a punch laser machine is presented. Based on a full-factorial experimental design, the parameters change of the properties of the joint environment by beading and change of the punch displacement are addressed. The influence on the properties of the clinched specimen is evaluated based on the variables Stiffness, force at the beginning of yielding and maximum force at head tensile loading and shear tensile loading. In addition, the geometric quality parameters of neck thickness, interlock and bottom thickness are evaluated. The relationships can be used to apply uniform loads to joints in joined structures to counteract oversizing.
Keywords: Sheet Metal; Joining; Stiffness

Ausbildung für alle? - Lippegaus, Petra (berufsbildung. Zeitschrift für Theorie- Praxis Dialog)

The Reasonable Investor, Ex Ante Information and Ad Hoc Announcements - Bartlitz, David; Gräfe, Alexander; Gilch, Luis (Consumer Behavioral Finance eJournal)

Unangemessene Benachteiligung durch Entgeltklausel in Ansparphase eines Bausparvertrags. Besprechung zu BGH, Urt. v. 15.11.2022 - XI ZR 551/21 - BGHZ 235, 102-117 - Bartlitz, David (iff Infobrief)

§§ 53, 54 GmbHG (Satzungsänderungen), Bd. 2: §§ 35-88 GmbHG, EGGmbHG - Bartlitz, David; Hoffmann, Jochen (Kommentar zum Gesetz betreffend die Gesellschaften mit beschränkter Haftung (GmbH-Gesetz))

Die Rechtfertigung des Kapitalismus und die Kritik. Der neue Geist des Kapitalismus von Luc Boltanski und Ève Chiapello - Knoll, Lisa (Soziologische Gegenwartsdiagnosen 3)

Förderung von digitalisierungsbezogenen Kompetenzen von angehenden Physiklehrkräften mit dem SQD-Modell im Projekt DiKoLeP - Weiler, David Christoph; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Lehr-Lern-Labore und Digitalisierung)

Lichtgeschwindigkeit in Flüssigkeiten mit LiDAR Measuring messen - Weiler, David Christoph; Bewersdorff, Arne; Wilhelm, Thomas; Kuhn, Jochen (Physik in unserer Zeit)

Predicting the development of digital media PCK/TPACK: The role of PCK, motivation to use digital media, interest in and previous experience with digital media - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Haagen-Schützenhöfer, Claudia; Riese, Josef; Weiler, David Christoph (Computers & Education)

Theoretische Sensibilität, Kodieren und all is data: Das Potenzial der Grounded Theory Methodology für die empirische Unterrichtsforschung - Müller, Jennifer (Empirische Unterrichtsforschung in DaFZ)
In diesem Beitrag wird das Potenzial der Grounded Theory Methodology im Kontext (fremd- und zweitsprachen-)didaktischer Forschung vorgestellt. Dabei werden insbesondere die zunehmende theoretische Sensibilität des bzw. der Forschenden während des Forschungsprozesses, das Kodieren und Kategorisieren als Möglichkeit des Erkenntnisgewinns und das Diktum all is data zur Berücksichtigung vielfältiger Perspektiven fokussiert. Zur Veranschaulichung werden Auszüge einer interdisziplinären Dissertation zu den Herausforderungen von ehemaligen Intensivklassenschüler*innen im Geschichtsunterricht herangezogen.

Couture von Frauen für Frauen - Kraft, Kerstin; Haller, Melanie

A combustion chemistry study of tetramethylethylene in a laminar premixed low-pressure hydrogen flame - Bierkandt, Thomas; Hemberger, Patrick; Oßwald, Patrick; Gaiser, Nina; Hoener, Martin; Krüger, Dominik; Kasper, Tina; Köhler, Markus (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Thermal and chemical structure of ethanol and 2-ethylhexanoic acid/ethanol SpraySyn flames - Gonchikzhapov, Munko; Kasper, Tina (Applications in Engery and Combustion Science)
Flame spray pyrolysis is intensively developing as a promising method of nanoparticle synthesis. The experimentally measured chemical and thermal structure of the spray flame is critically needed as a validation target for simulations of the synthesis of nanoparticles in these spray flames. This paper presents an experimental study of the chemical and thermal structure of the flame produced by the SpraySyn burner. The spatial distribution of the main species is obtained by microprobe sampling in combination with orthogonal time-of-flight mass spectrometry. The temperature distribution is obtained by a micro-thermocouple technique. The presented species and temperature data are discussed in the context of their experimental uncertainties and the plausibility of the flame structure.

Die Offenbarung des Johannes. - Bergmann, Claudia Dorit (Evangelische Orientierung)